Method for testing saturated surface dry water absorption rate of light and fine aggregate
By improving the operation steps of the wet mark method, including using a drying box and a mobile phone camera to test the dry water absorption rate of the saturated surface of the light fine aggregate, the problem that the existing method is not suitable for light fine aggregate, achieving more efficient and Accurate test results.
Patent Information
- Application Number
- CN202311007856.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-18
AI Technical Summary
The existing dry water absorption test method for saturated surfaces of light and fine aggregates is not suitable for light and fine aggregates, which leads to distortion of the test results and it is difficult to accurately determine their water absorption.
The steps to improve the operation of the wet mark method include blow drying using a drying box, and water mark observation using the back of a dark mirror and a mobile phone camera to ensure the accuracy and efficiency of the test.
It improves the accuracy and efficiency of the dry water absorption rate of the saturated surface of light and fine aggregates, and is suitable for the testing of light and fine aggregates, providing more objective and accurate test results.
Smart Images

Figure CN119470132A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for testing the saturated surface dry water absorption rate of light fine aggregate, belonging to the technical field of testing. Background Art
[0002] There are two definitions of water in the water-cement ratio. The first definition refers to the total amount of water in concrete, which is based on the specification "Ordinary Concrete Mix Design Code" (JGJ55-2011). The second definition refers to the amount of water used after deducting the water absorbed by aggregates from the total amount of water used, which is based on the specification "Hydraulic Concrete Mix Design Code" (DLT5330-2005). The British specification "Concrete-part1: Specification, performance, production and conformity" (BSEN206-1: 2000) clearly puts forward the concept of effective water use. Effective water use refers to the amount of water in fresh concrete after deducting the water absorbed by aggregates, and the water-cement ratio refers to the mass ratio of effective water use to cement in fresh concrete.
[0003] For aggregates with high water absorption, the water-cement ratio calculated by the two definitions is very different. The "Code for Design of Ordinary Concrete Mix" did not take into account the influence of aggregate water absorption when defining the water-cement ratio. Therefore, the "Code for Design of Hydraulic Concrete Mix" is more in line with engineering practice. This concept also provides ideas for a constant water-cement ratio when designing concrete mixes.
[0004] However, this also puts forward new requirements for the project, and it is necessary to clarify the amount of water absorbed by the aggregate. Therefore, the researchers proposed the concept of the saturated surface dry state of aggregate. The saturated surface dry state refers to the state in which the pores in the aggregate that can be penetrated by water are filled with water, but there is no free water on the surface of the particles. In this state, the aggregate neither absorbs water from the cementitious material nor releases water into the cementitious material. Therefore, it can be clearly stated that the amount of water absorbed by the aggregate is the water requirement when it reaches the saturated surface dry state. The saturated surface dry water absorption rate of aggregate refers to the percentage of water content of sand in the saturated surface dry state to the mass of sand in the dry or saturated surface dry state.
[0005] The test method for the saturated surface dry water absorption rate of aggregates can be found in multiple domestic and foreign specifications, such as the "Highway Engineering Aggregate Test Code" (JTG E42-2005) issued by the Ministry of Transport of my country, the "Hydraulic Concrete Test Code" (SL352-2020) issued by the Ministry of Water Resources of my country, the national standard "Sand for Construction" (GB / T 14684-2022) of China, and the British standard "Testing aggregates. Part 2. Methods of determination of density" (BS 812-1995). The test process can be divided into three main steps. The first is to blow dry the wet sand. The wet sand is gradually blown dry by a hair dryer. The second is to use various experimental methods (such as the trial mold method, the wet mark method, etc.) to determine whether the sand has been blown dry to the saturated surface dry state. If the saturated surface dry state is reached, stop blowing and proceed to the next step; if the saturated surface dry state is not reached, continue blowing until the sand reaches the saturated surface dry state. The third step is to weigh the saturated surface dry sand, then dry the saturated surface dry sand to absolute dryness, weigh it again, and calculate the moisture content of the saturated surface dry sand.
[0006] However, in the mold test method, since light and fine aggregate is a material that is not easy to collapse, it is already in an oversaturated surface dry state when it collapses, and the measured saturated surface dry water absorption rate result is distorted. Therefore, the mold test method is only applicable to ordinary fine aggregate, but not to light and fine aggregate. Therefore, light and fine aggregate can only be tested using the wet mark method, but the operating steps of the wet mark method still have some shortcomings, making it still not applicable to light and fine aggregate, and it needs to be improved. Summary of the invention
[0007] In view of this, in order to solve the problem that the saturated surface dry water absorption rate of light fine aggregate is difficult to measure, the present invention improves the operation steps of the wet mark method to make it suitable for light fine aggregate. The test method is simple to operate, quick to test, and the test results are objective and accurate.
[0008] In order to achieve the purpose of the present invention, the following technical solutions are provided.
[0009] A method for testing the dry water absorption rate of saturated surface of construction sand comprises the following steps:
[0010] Step 1: Use the quartering method to take out about 1100g of light and fine aggregate, put the aggregate into a drying oven at 105° to dry until it is weighed, and then evenly put it into two trays. First record the weight of the tray, and then record the total weight of the dry aggregate plus the tray;
[0011] Step 2: Add water until the aggregate floats. Add a small amount of water to one portion, let it stand for 24 hours, then put it into a drying oven and dry it at 70° until there is only a small amount of water on the surface of the aggregate. Take out the drier portion, record the total weight, and then conduct the test;
[0012] Step 3: Take out a little sample and place it on the back of the dark mirror that has been wiped clean. Tap it 10 times and then wipe the rest of the back of the mirror.
[0013] Step 4: Remove the surface within 1-3 seconds after flattening. Use the mobile phone camera to observe that the first wet mark disappears within 2 seconds, which means the surface is saturated and dry.
[0014] Step 5: Take out M = 500g saturated surface dry sample and dry it at 105° with air blast until it reaches constant weight and record the aggregate weight M1 at this time. The saturated surface dry water absorption rate of the aggregate is Q = (M-M1) / M1*100%;
[0015] Step 6: Then take out another sample and repeat the above process. The difference between the two results should not be greater than 3% of the average value, otherwise it will be invalid and retested.
[0016] Furthermore, in step 2, the light fine aggregate is hollow glass microspheres with a true density of 0.4 g / cm3 and a particle size of 90% < 90 μm.
[0017] Furthermore, the weighing device in step 1 is an electronic balance with a weighing accuracy greater than or equal to 0.1 g.
[0018] Furthermore, the suitable blast drying temperature in step 2 is 70°, because this temperature effectively prevents the dehydration of the aggregate, and part of the water is still trapped in the pores or mesopores of the aggregate.
[0019] Furthermore, in step 2, the amount of water added is 50ML.
[0020] Furthermore, in step 3, the back of the dark mirror is in accordance with the US ASTM C128-2015 and domestic SL352-2020 specifications, which require a flat, dry, clean, dark or matte non-absorbent surface, such as a rubber sheet or a black painted metal surface. The back of the mirror meets the requirements and it has been found through experiments that the disappearance process of water marks can be observed more clearly than other surfaces.
[0021] Furthermore, in step 4, in order to determine the water mark observation effect, first press the surface of the sample with your fingers and then print it on the back of the mirror to find the conditions under which the water marks can be clearly observed. The experiment found that the best observation environment is a slightly dark place indoors, the best observation position is the diffuse reflection of light on the back of the mirror, and the best observation angle is to look at it from the side.
[0022] Furthermore, in step 4, if the average disappearance time of the water marks is observed to exceed 2s, pour the aggregate back into the tray, stir it evenly to loosen it, weigh it and record it, and then dry it at 70° for 5min. After taking it out, record the actual drying time and the total weight at this time, and continue the test according to the above steps.
[0023] Furthermore, in step 4, if no water marks are observed, it means that the surface is oversaturated and dry. The sample should be evenly sprayed with 50 ml of water, covered with plastic wrap and left to stand for 30 minutes before continuing the test.
[0024] Beneficial Effects
[0025] (1) The present invention provides a method for testing the saturated surface dry water absorption rate of light fine aggregate. The method is improved based on the wet mark method, which solves the problem that the saturated surface dry water absorption rate of light fine aggregate is difficult to test, and can greatly improve the accuracy and efficiency of light fine aggregate saturated surface dry water absorption detection.
[0026] (2) The present invention provides a method for testing the saturated surface dry water absorption rate of light and fine aggregate, which uses a drying box for air drying instead of a handheld hair dryer, so that the light and fine aggregate is not easily blown away and is dried more evenly.
[0027] (3) The present invention provides a method for testing the saturated surface dry water absorption rate of light fine aggregate. The air drying temperature is 70°. According to relevant research, this temperature can effectively prevent the dehydration of the aggregate, and some water is still trapped in the pores or mesopores of the aggregate.
[0028] (4) The present invention provides a method for testing the dry water absorption rate of a saturated surface of construction sand. The wet mark method is based on the requirements of the U.S. ASTM C128-2015 and domestic SL352-2020 specifications. It is a flat, dry, clean, dark or matte non-absorbent surface, such as a rubber sheet or a metal surface painted black. The present invention uses the back of a dark mirror. The back of the mirror meets the requirements and it has been found through experiments that, compared with other surfaces, it can more clearly observe the disappearance process of the water mark.
[0029] (5) The present invention provides a method for testing the dry water absorption rate of the saturated surface of construction sand, which uses a mobile phone camera instead of the human eye for observation, and the best observation environment is a slightly dark place indoors and the observation position is the diffuse reflection point of the back of the mirror. Because the mobile phone camera can increase the contrast between the water mark and the surrounding dry surface, and can record video, unlike human eye observation which is subjective and prone to misjudgment, the observation result is more accurate. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the operation diagram of step 3
[0031] Figure 2 The process of removing water marks from mobile phone cameras
[0032] Figure 3 Schematic diagram of the mold for the trial mold method in the comparative example DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific implementation modes.
[0034] Example 1
[0035] A method for testing the saturated surface dry water absorption of light fine aggregate comprises the following steps:
[0036] Step 1: Use the quartering method to take out about 1100g of hollow glass microspheres, the true density of hollow glass microspheres is 0.4g / cm3, and the particle size is 90% <90μm. Put the aggregates into a drying oven at 105° and dry them until they are weighed. Then put them evenly into two trays. First record the weight of the trays, and then record the total weight of the dry aggregates and the trays.
[0037] Step 2: Add water until the aggregate floats, add 50ml of water to one portion, let it stand for 24 hours, then put it into a drying oven and dry it at 70° until there is only a small amount of water on the surface of the aggregate. Take out the drier portion, record the total weight, and then conduct the test;
[0038] Step 3: Take out a little sample and place it on the back of the dark mirror that has been wiped clean. Tap it 10 times and then wipe the rest of the back of the mirror.
[0039] Step 4: Remove the surface within 1-3 seconds after flattening. Use the mobile phone camera to observe that the first wet mark disappears within 2 seconds, which means the surface is saturated and dry.
[0040] Step 5: Take out M = 500g saturated surface dry sample and dry it at 105° with air blast until it reaches constant weight and record the aggregate weight M1 at this time. The saturated surface dry water absorption rate of the aggregate is Q = (M-M1) / M1*100%;
[0041] Step 6: Then take out another sample and repeat the above process. The difference between the two results should not be greater than 3% of the average value, otherwise it will be invalid and retested.
[0042] Comparative Example 1
[0043] A method for testing the saturated surface dry water absorption of light fine aggregate comprises the following steps:
[0044] Step 1: Use the quartering method to take out about 1100g of hollow glass microspheres, the true density of hollow glass microspheres is 0.4g / cm3, and the particle size is 90% <90μm. Put the aggregates into a drying oven at 105° and dry them until they are weighed. Then put them evenly into two trays. First record the weight of the trays, and then record the total weight of the dry aggregates and the trays.
[0045] Step 2: Add water until the aggregate floats, add 50ml of water to one portion, let it stand for 24 hours, then put it into a drying oven and dry it at 70° until there is only a small amount of water on the surface of the aggregate. Take out the drier portion, record the total weight, and then conduct the test;
[0046] Step 3: Mix the aggregate evenly and pour it loosely into the saturated dry test mold. After filling, let the tamping rod fall freely about 0.5 cm from the surface and tamp it 10 times. Continue to fill it up and tamp it 10 times. Do this 3 and 2 times and then smooth the surface.
[0047] Step 4: Slowly lift the test mold. When the sample collapses for the first time, it reaches the saturated surface dry state of the test mold method. If it collapses too much, spray 50ml of water evenly on the aggregate, cover it with plastic wrap and let it stand for 30 minutes before retesting.
[0048] Step 5: Then take out another sample and repeat the above process. The difference between the two results should not be greater than 3% of the average value, otherwise it will be invalid and retested.
[0049] Comparative Example 2
[0050] A method for testing the dry water absorption rate of saturated surface of artificial sand comprises the following steps:
[0051] Step 1: Use the quartering method to take out about 1100g of artificial sand, the true density of artificial sand is 0.4g / cm3, and the particle size is 90% <200μm. Put the aggregate into a drying oven at 105° and dry it until it is weighed. Then put it evenly into two barrels. First record the weight of the barrel, and then record the total weight of the dry aggregate and barrel.
[0052] Step 2: Add water until the water level is two centimeters above the aggregate, stir evenly for 5 minutes, cover with film and let stand for 24 hours, then carefully scoop out the upper clear water, and do not scoop out the turbid liquid containing fine powder, and let one portion retain a small amount of water, put it in a drying oven at 70° and dry it with air until there is only a small amount of water on the surface of the aggregate, take out the drier portion, record the total weight and then conduct the test;
[0053] Step 3: Mix the aggregate evenly and pour it loosely into the saturated dry test mold. After filling, let the tamping rod fall freely about 0.5 cm from the surface and tamp it 10 times. Continue to fill it and tamp it 10 times. Do this 3 and 2 times and then smooth the surface.
[0054] Step 4: Slowly lift the test mold. When the sample collapses for the first time, it reaches the saturated surface dry state of the test mold method. If it collapses too much, spray 50ml of water evenly on the aggregate, cover it with plastic wrap and let it stand for 30 minutes before retesting.
[0055] Step 5: According to the US ASTM C128-2015 and domestic SL352-2020 specifications, the temporary surface test method is then used for testing. Generally, the results of the temporary surface test method will be greater than those of the trial mold method. In order to contrast with the trial mold method, the trial mold method is selected for testing first, and then the upper half of the cone is taken to continue the temporary surface test method.
[0056] Step 6: Place the sample on the back of a dark mirror that has been wiped clean, restrain the periphery of the sample and compact it, then wipe the rest of the back of the mirror clean;
[0057] Step 7: Remove the sample and use the mobile phone camera to observe that the wet mark disappears within 2 seconds for the first time, which is the saturated surface dry state of the wet mark method;
[0058] Step 8: Take out M = 500g saturated surface dry sample and dry it at 105° with air blast until it reaches constant weight and record the aggregate weight M1 at this time. The saturated surface dry water absorption rate of the aggregate is Q = (M-M1) / M1*100%;
[0059] Step 9: Then take out another sample and repeat the above process. The difference between the two results should not be greater than 3% of the average value, otherwise it will be discarded and retested.
[0060] The data are shown in Table 1
[0061] Trial mold method Wet Mark Method Hollow glass microspheres 0.36% 90.17% Artificial sand 3.73% 5.64%
Claims
1. A method for testing the saturated surface dry water absorption of light fine aggregate, characterized in that: The method comprises the following steps: Step 1: Use the quartering method to take out about 1100g of light and fine aggregate, put the aggregate into a drying oven at 105° to dry until it is weighed, and then evenly put it into two trays. First record the weight of the tray, and then record the total weight of the dry aggregate plus the tray; Step 2: Add water until the aggregate floats. Add a small amount of water to one portion, let it stand for 24 hours, then put it into a drying oven and dry it at 70° until there is only a small amount of water on the surface of the aggregate. Take out the drier portion, record the total weight, and then conduct the test; Step 3: Take out a little sample and place it on the back of the dark mirror that has been wiped clean. Tap it 10 times and then wipe the rest of the back of the mirror. Step 4: Remove the surface within 1-3 seconds after flattening. Use the mobile phone camera to observe that the first wet mark disappears within 2 seconds, which means the surface is saturated and dry. Step 5: Take out M = 500g saturated surface dry sample and dry it at 105° with air blast until it reaches constant weight and record the aggregate weight M1 at this time. The saturated surface dry water absorption rate of the aggregate is Q = (M-M1) / M1*100%; Step 6: Then take out another sample and repeat the above process. The difference between the two results should not be greater than 3% of the average value, otherwise it will be invalid and retested.
2. A method for testing saturated surface dry water absorption of light fine aggregate according to claim 1, characterized in that: The weighing device in step 1 is an electronic balance with a weighing accuracy greater than or equal to 0.1g.
3. A method for testing saturated surface dry water absorption of light fine aggregate according to claim 1, characterized in that: The suitable blast drying temperature in step 2 is 70°. According to relevant research, this temperature can effectively prevent the dehydration of the aggregate, and some water is still trapped in the pores or mesopores of the aggregate.
4. A method for testing saturated surface dry water absorption of light fine aggregate according to claim 1, characterized in that: In step 2, the amount of water added is 50ML.
5. A method for testing saturated surface dry water absorption of light fine aggregate according to claim 1, characterized in that: In step 3, the back of the dark mirror is based on the US ASTM C128-2015 and domestic SL352-2020 specifications, which require a flat, dry, clean, dark or matte non-absorbent surface, such as a rubber sheet or a black painted metal surface. The back of the mirror meets the requirements and it has been found through experiments that the disappearance process of water marks can be observed more clearly than other surfaces.
6. A method for testing saturated surface dry water absorption of light fine aggregate according to claim 1, characterized in that: In step 4, in order to determine the water mark observation effect, first press the surface of the sample with your fingers and then print it on the back of the mirror to find the conditions under which the water marks can be clearly observed. The experiment found that the best observation environment is a slightly dark place indoors, the best observation position is the diffuse reflection of light on the back of the mirror, and the best observation angle is to look at it from the side.
7. A method for testing saturated surface dry water absorption of light fine aggregate according to claim 1, characterized in that: In step 4, if the average disappearance time of water marks is observed to exceed 2s, pour the aggregate back into the tray, stir evenly to loosen it, weigh and record it, and then dry it at 70° for 5 minutes. After taking it out, record the actual drying time and the total weight at this time, and continue the test according to the above steps.
8. A method for testing saturated surface dry water absorption of lightweight fine aggregate according to claim 1, characterized in that: In step 4, if no water marks are observed, it means that the surface is oversaturated and dry. The sample should be evenly sprayed with 50 ml of water, covered with plastic wrap and left to stand for 30 minutes before continuing the test.